Information Security of Russia in the Digital Economy: The Economic and Legal Aspects - FROLOVA, Evgenia Evgenevna; POLYAKOVA, Tatyana Anatolevna; DUDIN, Mihail Nikolaevich; RUSAKOVA, Ekaterina Petrovna; KUCHERENKO, Petr Aleksandrovich (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
Contemporary realities dictate that technologization, digitalization (transition of the economy and the social sector to digital technologies of functioning and interaction) and the national intellectual capital are the basic competitive advantages of the country that require proper information security. An information security system is a set of corporate rules, standards of work and procedures for ensuring information security formed based on the audit of the company's information system, and the analysis of existing security risks in accordance with requirements of the regulatory documents of the Russian Federation and the provisions of the standards in the field of information security. It is especially important for Russian companies actively interacting with foreign partners. In addressing the problem of information security, the development of the company's unified information security policy occupies a leading place; therefore, this article will be devoted to consideration of these issues. The authors of the present study proceed from the objective-subjective predetermination of any phenomena and processes of the external world. In this format, the study is based on general scientific methods: systematic analysis and generalization of normative and practical materials; formal and dialectical logic: analysis, synthesis, induction, deduction, hypotheses, analogies; and special methods of legal research: comparative-legal and historical-legal, system analysis and interpretation of legal norms. Based on the analysis, the following conclusions have been made: currently, the most important direction of the national economy development is the protection of vital human and social interests, the key element of which is information security. This study represents the development of a scientific overview of the modern ways to ensure information security in both applied and legal contexts. This article underlines and examines the problems and economic legal features of ensuring information security in Russia. These materials can be used both in preparation of other scientific research and in the development of guidance documents by the power structures.